Pelatihan Canva for Teachers Membuat Bahan Ajar yang Menarik dan Efektif - Nuridayanti; Dyah Vitalocca; Elfira Makmur; Nurul Mukhlisah Abdal; Hilda Ashari (Vokatek: Jurnal Pengabdian Masyarakat, 2023)
Teachers at SD Inpres Bonto-Bontoa currently employ conventional teaching models, while students are more inclined towards technology-based instruction. Therefore, efforts are needed to bridge this gap through the implementation of training sessions. The objective of this community service is to provide training to elementary school teachers on the application of teaching methods using the Canva for Education application, aiming to make the teaching methods applied by teachers more engaging. The community service was carried out directly in the IT Room of SD Inpres Bonto-Bontoa, involving 20 teachers and attended by school supervisors, the principal, several professors, and assisted by students. The implementation of community service at SD Inpres Bonto-Bontoa, facilitated in the form of Canva For Education training, has had a positive impact on enhancing teachers' skills in developing teaching materials, serving as a crucial step in technology adaptation within the education environment.